Limbal Stem Cell Deficiency—Demography and Underlying Causes - Vazirani, Jayesh; Nair, Dhanyasree; Shanbhag, Swapna; Wurity, Siva; Ranjan, Abhishek; Sangwan, Virender (American journal of ophthalmology, 2018)
To determine the demographic features of patients affected by limbal stem cell deficiency (LSCD), and to identify the underlying causes of LSCD. Retrospective, multicenter case series. Setting: Two large tertiary care ophthalmology hospitals. Subjects: Patients with a diagnosis of LSCD presenting from January 1, 2005 to December 31, 2014. Records of patients with a clinical diagnosis of LSCD were reviewed. Demographic details and clinical features at presentation, as well as the underlying cause of LSCD (if identified), were noted. Descriptive statistical analysis and chart preparation were done. Main outcome measures were type of LSCD (unilateral or bilateral), age and sex of patients, extent of LSCD (clock hours of limbus involved), and underlying cause of LSCD. We found 1331 patients with LSCD in the 10-year period under study. Unilateral LSCD was more common (791 patients) than bilateral LSCD (540 patients). Out of 1331 patients, 875 (65.74%) were male. The median age of patients was 24 years. Extent of LSCD could be determined in 1849 eyes, of which 1239 eyes (67.00%) had total LSCD. The underlying cause of LSCD could be identified in 1512 eyes. In cases of unilateral LSCD, ocular surface burns was the commonest identifiable cause (83.73%). The leading identifiable causes of bilateral LSCD were ocular surface burns (29.95%), allergic conjunctivitis (29.48%), Stevens-Johnson syndrome (SJS) or toxic epidermal necrolysis (TEN) (23.11%), aniridia (9.43%), and mucous membrane pemphigoid (3.54%). Lime (“chuna”) injury was responsible for ocular surface burns in 352 out of 567 cases in which the agent was identified (62.08%). In our study, unilateral LSCD was more common than bilateral LSCD. Young male subjects were commonly affected, with a majority of eyes suffering from total LSCD. Overall, ocular surface burns are the leading cause of LSCD. Unilateral and bilateral LSCD had a markedly different distribution of causes, necessitating different approaches to management.